Investigation on frosting and defrosting performance of superhydrophobic metal additively manufactured materials - Yew, Yun Chian (Nanyang Technological University, 2024)
In this final year project, frosting and defrosting performance of superhydrophobic surfaces on tubes were investigated. The motivation to investigate superhydrophobic surfaces to enhance anti-frosting/defrosting stems from previously found mechanism that the higher contact angle on such surfaces caused condensate to undergo self-propelled jumping. Such mechanism has the potential to enable the removal of droplets from the surface before freezing occurs. Comparisons were made between conventional metal aluminium, Al6061, and additively manufactured (AM) metal, AlSi10Mg, in terms of their frost surface area coverage and average frost thickness. To enhance the anti-frosting capabilities of both metal alloys, chemical etching using hydrochloric acid and boehmitization were used as methods to form micro/nanostructures on the surface of the tubes. The experimental results showed that AM metal possessed lower frost surface coverage than Al6061 across all three tested temperatures of -7˚C, -10˚C and -13˚C. Building on the better anti-frosting capability of AM metal and the unique surface morphology because of the selective laser melting process, the duration of chemical etching was varied for AM metal. It was found that for chemical etching duration from 3 min to 10 min, AM metal had better frost retardation with increasing chemical etching duration, with a 12% frost surface area coverage reduction as etching time increases. However, between etching time of 10 min and 15 min, there is no significant difference in the frost retardation rate of AM metal. In addition, the influences of heat treatment process and surface contamination on the anti-frosting capabilities of AM metals were also explored. Deposition of dust particles on AM surface was found to cause increased frosting rate whereas heat treatment on AM metal was found to negatively affect the surface such that further chemical etching and boehmitization were unable to slow down frost formation. The durability of superhydrophobic AM surface was also studied. It was found that surface degradation occurs after frosting occurs at -13˚C, while repeated cycles of frosting at -10˚C did not cause any surface degradation. Finally, defrosting experiments were also carried out and it was shown that the hierarchical structures formed on both superhydrophobic surfaces of Al6061 and AM metals by chemical etching and boehmitization allowed dynamic defrosting to occur, thereby causing defrosting to occur faster on tubes that underwent surface treatment.